Low-temperature hydrothermal carbonization of pectin enabled by high pressure - Yu, Shijie; Zhao, Peng; Yang, Xiaoxiao; Li, Qinghai; Mohamed, Badr A.; Md Saad, Juniza; Zhang, Yanguo; Zhang, Yanguo; Zhou, Hui (Elsevier, 2022)
Pectin is an important component of biomass waste widely existing in the plant cell wall. Hydrothermal carbonization of pectin can produce carbon materials for energy storage, adsorption, and catalysis. However, pressure is generally the self-generated pressure in the hydrothermal reaction, which changes with temperature during the heating process. The independent effect of pressure on the hydrothermal reaction of pectin is unclear and has not been investigated before, especially the effect of high pressure at a low temperature. In this study, by performing the hydrothermal treatment of pectin under different pressures (up to 20 MPa) at a fixed temperature of 200 °C, we found that high pressure could effectively promote carbonization. To understand the mechanism of pressure effect on hydrochar properties, the produced hydrochars were characterized by elemental analysis, scanning electron microscopy (SEM), N2 adsorption/desorption, Fourier-transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), while pyrolysis and combustion behaviors were analyzed using the thermogravimetric analyzer (TGA). The mechanism of high pressure was cleaving the hydroxyl groups, ester carbonyl groups, and aliphatic structures with the process of dehydration and decarboxylation. More aromatic structures were formed in hydrochars with higher carbon content, resulting in a structure with better thermal stability. Carbon spheres with a larger diameter could be formed under higher pressure. The promoting effect was strongest in the range of 2–8 MPa and weaker under higher pressures (8–20 MPa). Future studies may improve the degree of hydrothermal carbonization of pectin by applying an appropriate high pressure.